Direct digestion of living cells via a gel-based strategy for mass spectrometric analysis. Issue 8 (12th January 2017) - Xiong, Yun; Zhang, Ying; Yao, Jun; Yan, Guoquan; Lu, Haojie
Abstract : A novel method was established for proteomic analysis, during which cells were absorbed into gel and directly digested into peptides. Abstract : A novel sample preparation method was established for proteomic analysis, during which living cells were absorbed into vacuum-dried polyacrylamide gel and directly digested into peptides for subsequent LC-MS/MS assays. As a consequence, both of the steps for cell lysis and protein extraction involved in a conventional digestion method were skipped.